THE ISOMORPHISM OF JESUIT LIBRARIES (XVI-XVIII CENTURIES) - de Tezanos, Araceli (Revista de Historia Social y de las Mentalidades, 2015)
n order to show the isomorphic nature of jesuit  libraries, the author did for the first time the  decoding and transcription of the old handwritten  inventories of the Jesuit libraries from the  Santiago, Concepción and Castro colleges  found in the “temporalidades jesuitas” at the  National  Archive of Chile (Archivo Nacional de  Chile, ANCH). To understand the structure and  development of libraries in the Society of Jesus,  some key concepts (scriptor-auctor/inventory- catalogue) are presented and explained in the  text including a reference to the history of the  different forms of cataloguing elaborated by the  Order. A cartography of the different libraries  that could be found in all the Jesuit colleges and  houses, their organization and the role of the  librarian in relation to the access to books are  presented. The concept of isomorphism, that in  mathematics implies a similitude relationship  between two objects and within group theory  permits to deduce the properties of one group  from the properties of the other, is applied to the  ensemble of libraries. This notion was used as the  tool to show through comparison of authors, that  the content of inventories and libraries catalogues  from eight Jesuit colleges elaborated during the  x VIII Century, share the presence of almost 300  authors, in different subjects. The isomorphism  of the Jesuit libraries is de representation of an  experience in common, a shared and transmissible  tradition and, finally, libraries become a  constitutive element of the collective memory of  the Order.
Keywords: Jesuit libraries; Cartography; Isomorphism